Enhancing the role of trade union in ensuring the right to employment in Vietnam - XUÂN THẢO, ĐINH; THỊ NGỌC HOA, KHẮC (Tạp chí Nghiên cứu Khoa học Công đoàn, 2019)
Trade union is a political-social organization of the working class and laborers, participating in governance of the stateand society, monitoring and overseeing activities of state agencies. Trade union is formed due to the demand of the mass of employeeswith a mandate to represent and protect legal rights and legitimate interests of employees, including the right to employment. The rightto employment is a fundamental human right stipulated in international law and national law. In Vietnam, the right to employment isconstitutionalized and specified in laws. With regards to ensuring the right to employment, trade union plays a crucial role, particularlyagainst the backdrop of our country developing a socialist-oriented market economy, accelerating industrialization and modernization,and in-depth and comprehensive international integration. Thus, there should be proper solutions to enhance the role for trade union toensure the right to employment.